A Promised Mindland?: A rectificatory theory-practice position for non-Indigenous researchers. Issue 4 (November 2014) - Puch-Bouwman, Jen
Non-Indigenous researchers who study Indigenous people and issues are situated in a highly contested epistemological space. Indigenous sovereignty and decolonizing endeavours have transformed this realm into a thriving liberatory arena. That in turn has stirred colonial residues in the field and has led non-Indigenous researchers to readjust their ideologies and practices vis-à-vis the Indigenous epistemological insurgence. In order to respond to these challenges, researchers may turn to a range of theory-practice positions. I review these positions and suggest that, despite their immense contributions, they still constitute higher-level symptoms of the colonial aftermath. Therefore, a rectificatory theory-practice position is proposed, advocating resistance, trans-generational justice and reparation by non-Indigenous researchers in Indigenous-related research. In addition, I introduce the concept of "mindland" to encompass the rectification of both knowledge and land, and highlight the wider colonized context of Indigenous-related research.